Faktualisasi Nilai-Nilai Kebangsaan Berbasis UUD 1945 Pada Optimalisasi Kebijakan Pemerintah Berdasarkan Peraturan Mentri No.08 Tahun 2017 Terhadap Kontrak Gross Split di Sektor Migas Indonesia - Edy Soesanto; Diah Ayu Kusuma Ningrum; Mohamad Rizqi Putra Prasetyo (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
As a solution to overcome the problems in the Cost Recovery Production Sharing Contract system, the Government of Indonesia through the Ministry of Energy and Mineral Resources has issued Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 08 Year 2017 on Gross Split Production Sharing Contract. This new regulation was issued due to the decline in the discovery of oil and gas reserves and the decline in non-tax state revenue (PNBP) from the upstream oil and gas sector. The Gross Split Production Sharing Contract scheme also aims to reduce bureaucracy in investment to attract investors to conduct exploration and exploitation in Indonesia. This study aims to analyze the legal aspects related to Gross Split regulations in improving the investment climate in the upstream oil and gas sector, as well as to evaluate the role of the Oil and Gas Special Task Force as an institution responsible for controlling and supervising the activities of the Cooperation Contractor in the Production Sharing Contract.